Literasi Keuangan dan Sikap Keuangan: Implikasinya terhadap Perilaku Manajemen Keuangan melalui Hedonism Lifestyle - Mariska, Revi Sasti; Suseno, Novie Susanti; Kusmiati, Eti (Politeknik Negeri Jember, 2025)
The increasing consumptive behavior among Generation Z shows the need for an understanding of the factors that influence financial management. This study aims to examine the effect of financial literacy and financial attitudes on financial management behavior, with hedonism lifestyle as a mediating variable. Using a quantitative approach through survey method, this study involved 100 participants from Generation Z workforce in Garut Regency who were selected through accidental sampling technique. Data analysis was conducted using SEM-PLS method. The results showed that financial literacy and financial attitudes have a positive effect on financial management behavior, while hedonic lifestyle has a negative effect. In addition, hedonic lifestyle mediates the relationship between financial attitudes and financial management behavior. The findings confirm the importance of implementing financial literacy education into the school curriculum and job training programs, as well as the need for socialization to regulate consumptive lifestyles in order to foster a younger generation capable of making wise financial decisions.